Information-Modeling Forecasting System for Thermal Mode of Top Converter Lance - Zhul’kovskii, O. A.; Panteikov, S. P.; Zhul’kovskaya, I. I. (Steel in translation, 2022)
—On the basis of mathematical modeling and object-oriented programming, a computer information-modeling forecasting system (IMFS) for thermal mode of top lance barrel (TLB) of oxygen converter was developed in order to fulfill the urgent and economically feasible task of determining the compliance of input technological parameters with certain safety criteria for conducting converter melting. The program was created in the form of a Windows-oriented application by refining the previously developed mathematical model of the temperature mode of the top converter lance barrel using the object-oriented programming language C# in Microsoft Visual Studio 2019 IDE. The mathematical model provides the solution of differential heat conduction equation in cylindrical coordinates (two-dimensional formulation) with assignment of the initial (temperature distribution in the computational domain) and boundary conditions of the II and III kind (respectively, on the outer and inner surfaces of the TLB). The finite difference approximation of the heat conduction equation and boundary conditions was obtained by the integro-interpolation method (balance method). A numerical sweep method (modified Gauss method) and an unconditionally stable implicit scheme were used to calculate the temperature field. Thermophysical values were obtained by approximating the corresponding tabular values. The application does not put forward special requirements for the computer infrastructure, operates locally (without the need for access to Internet), does not require special skills to work with it, having an intuitive user interface: the working area of the program consists of three windows (sections), in which the results of calculating the thermal mode of the TLB are displayed. The developed IMFS allows evaluating the design and technological parameters of the top blowing device as a criterion for its safe operation. Its application in the “advisor” mode ensures the optimal design of the top oxygen lances with a rational water-cooling system in order to ensure the proper thermal mode of the TLB throughout the entire operation period, as well as trouble-free operation of the blowing device, which is especially important for the conditions of converter shops in Ukraine equipped with outdated designs of top lances with low service life.